Neutron scattering study of the dynamics of a polymer melt under nanoscopic confinement - Krutyeva, Margarita; Martin, Jaime; Arbe, Arantxa; Colmenero, Juan; Mijangos, Carmen; Schneider, Gerald J.; Unruh, Tobias; Su, Yixi; Richter, Dieter (Journal of Chemical Physics, 2009)
Poly(ethylene oxide) confined in an anodic aluminum oxide solid matrix has been studied by different neutron scattering techniques in the momentum transfer (Q) range 0.2 < Q=vertical bar Q vertical bar < 1.9 A degrees(-1). The cylindrical pores of the matrix present a diameter (40 nm) much smaller than their length (150 mu m) and are parallel and hexagonally ordered. In particular, we investigated the neutron intensity scattered for two orientations of the sample with respect to the incident beam, for which the Q direction was either parallel or perpendicular to the pores for a scattering angle of 90 degrees. Diffuse neutron scattering at room temperature has shown that the aluminum oxide has amorphous structure and the polymer in the nanoporous matrix is partially crystallized. Concerning the dynamical behavior, for Q < 1 A degrees(-1), the spectra show Rouse-like motions indistinguishable from those in the bulk within the uncertainties. In the high-Q limit we observe a slowing down of the dynamics with respect to the bulk behavior that evidences an effect of confinement. This effect is more pronounced for molecular displacements perpendicular to the pore axis than for parallel displacements. Our results clearly rule out the strong corset effect proposed for this polymer from nuclear magnetic resonance (NMR) studies and can be rationalized by assuming that the interactions with the pore walls affect one to two adjacent monomer monolayers.
Keywords: aluminium compounds; anodes; monolayers; neutron diffraction; nuclear magnetic resonance; polymer melts; polymers